Effect of a saffron extract on sleep quality in adults with moderate insomnia: A decentralized, randomized, double-blind, placebo-controlled trial - Julius Schuster; Christin Mundhenke; Hannah Nordsieck; Camille Pouchieu; Line Pourtau; Andreas Hahn (Sleep Medicine: X, 2025)
Aim: Natural interventions for sleep disturbances, such as saffron extract, are gaining scientific and clinical interest. This 3-arm, randomized, double-blind, placebo-controlled trial examined the effect of a standardized saffron extract (Safr’Inside™) on sleep, stress, and other associated psychological outcomes in 165 adults reporting moderate insomnia. Methods: Participants received 30 mg, 20 mg saffron extract, or placebo for 4 weeks. The primary endpoint was the change in insomnia symptoms (Athens Insomnia Scale, AIS). Secondary outcomes were the Single-Item Sleep Quality Scale (SQS), Perceived Stress Scale (PSS), Patient Health Questionnaire-4 (PHQ-4), Positive and Negative Affect Schedule (PANAS), Epworth Sleepiness Scale (ESS), and World Health Organization Quality of Life (WHOQOL). Analyses followed an intention-to-treat (ITT) approach, with per-protocol (PP) confirmation. Results: Among 150 completers, saffron extract led to a greater reduction in insomnia symptoms (AIS) than the placebo (between-group adjusted mean difference β = −0.95 [95 % CI: −1.79, −0.11], P < .05). In secondary analyses, sleep quality (SQS) improved significantly after 3 weeks and was sustained at week 4 in both saffron groups compared to placebo (30 mg vs placebo: β = 0.82 [95 % CI: 0.22, 1.41], P = .004; 20 mg vs placebo: β = 1.02 [0.43, 1.62], P < .001). Perceived stress (PSS) was significantly reduced with 30 mg or 20 mg saffron extract compared to placebo (30 mg vs placebo: β = −1.87 [95 % CI: −3.23, −0.53], P = .01; 20 mg vs placebo: β = −1.89 [95 % CI: −3.22, −0.52], P = .04). Some improvement in psychological symptoms (PHQ-4) was also observed with 30 mg saffron extract compared to placebo (β = −0.79 [−1.40, −0.18], P = .03). All other measures showed no significant differences. No serious adverse events occurred. Conclusions: Four weeks of 20 or 30 mg saffron extract may reduce insomnia and stress in middle-aged adults. Future research should assess longer interventions and explore which subgroups benefit most from saffron extract.